GERMINATION RATE OF PENNISETUM GLAUCUM SEEDLING IN FUCTION OF SALINE STRESS, GROWTH AND BIOMASS OF AERIAL PART AND ROOT - LUCENA, Leandro Ricardo Rodrigues de; SIMÕES, Vicente José Laamon Pinto; BEZERRA, Cinara Wanderléa Felix; IZIDRO, José Lypson Pinto Simões; SOUZA, Marcondes Sá; LEITE, Maurício Luiz de Mello Vieira (Brazilian Journal of Biometrics, 2019)
Millet is an annual cycle plant, with C4 metabolism, tolerant to water deficit, and it is cultivated in regions with scarcity of rain. The objective was to evaluate the germination of the millet seedling in function of saline stress, growth and biomass of the aerial part and the root system. The experiment was performed in a completely randomized design, with four treatments and five replicates, with the unit being represented by seeds of millet. The treatments were constituted by solutions with addition of NaCl corresponding to 2.337, 4.674 and 7.011 g/L, respectively for the electrical conductivities 4.0; 8.0; 12.0 dS/m and 0 dS/m (distilled water) as control. The millet cultivar used in this experiment was the IPA Bulk 1BF. The mean germination rate of seedlings in relation to control salinity level was higher than 90%, while for level of 12 dS.m-1 salinity there was no germination. The fitted model presented a high coefficient of determination (pseudo-R²= 90.96%) and low sum of squares of residuals (SSR=0.26). The beta regression model proved to be an appropriate option to analyse the millet seedling germination rate after 72 hours in function of salinity level, length of the root system and dry mass of the aerial part.